Effect of the Thermophilic Bacterial Biculture Consortium from Mudiak Sapan Hot Springs on Biofuel Production - Irdawati Irdawati; Fahra Fahra; Dwi Hilda Putri; Dezi Handayani; Yusrizal Yusrizal (Jurnal Penelitian Pendidikan IPA, 2023)
Biofuels are fuels derived from biomass and consist of biogas, biodiesel and bioethanol. Bioethanol is a biofuel whose main ingredients are from plants and generally use microorganisms in the fermentation process. One way is to use thermophilic bacteria with the advantage of low contamination levels and better product quality. Bacteria that exist in nature are not only in a single form but also exist in the form of a consortium in which there are beneficial or detrimental bacterial interactions. Favorable bacterial interactions indicate that the bacteria are compatible. Using a consortium with compatible bacteria gives better results than using a single bacteria. This study aims to determine the compatibility and effect of a consortium of thermophilic bacteria from Mudiak Sapan hot springs on biofuel yields. This research is a descriptive research. To test the cooperation between isolates, a compatibility test was carried out using the disk diffusion method. Then the biculture consortium isolates of thermophilic bacteria were fermented in liquid TMM medium (Thermophilic Minimum Media) and the bioethanol content was measured using a distillation apparatus. The results of this study showed that the six pairs of compatible consortium and MS 9-12 consortium produced the highest bioethanol, namely 1.0003%. Then the biculture consortium isolates of thermophilic bacteria were fermented in liquid TMM medium (Thermophilic Minimum Media) and the bioethanol content was measured using a distillation apparatus. The results of this study showed that the six pairs of compatible consortium and MS 9-12 consortium produced the highest bioethanol, namely 1.0003%. Then the biculture consortium isolates of thermophilic bacteria were fermented in liquid TMM medium (Thermophilic Minimum Media) and the bioethanol content was measured using a distillation apparatus. The results of this study showed that the six pairs of compatible consortium and MS 9-12 consortium produced the highest bioethanol, namely 1.0003%.